Processing and properties of advanced ceramics and composites. - Singh, J. P. (Ceramic transactions, 2014)
With contributed papers from the 2011 Materials Science and Technology symposia, this is a useful one-stop resource for understanding the most important issues in the processing and properties of advanced ceramics and composites. Logically organized and carefully selected, the articles cover the themes of the symposia: Innovative Processing and Synthesis of Ceramics, Glasses and Composites; Advances in Ceramic Matrix Composites; Solution-Based Processing of Materials; and Microwave Processing of Materials. A must for academics in mechanical and chemical engineering, materials and or ceramics,